THE IMPORTANCE OF NONVERBAL COMMUNICATION IN THE TEACHING PROCESS: THE IMPORTANCE OF NONVERBAL COMMUNICATION IN THE TEACHING PROCESS - Allanazarova, Feruza (Журнал иностранных языков и лингвистики, 2025)
Nonverbal communication plays a crucial role in the effectiveness of the teaching and learning process. While verbal communication conveys the content of a lesson, nonverbal cues such as facial expressions, gestures, posture, and eye contact support classroom management, enhance student engagement, and contribute to a more dynamic and interactive learning environment. This thesis explores the multifaceted importance of nonverbal communication in teaching, especially in second language classrooms, where visual and emotional cues can significantly enhance comprehension. Through literature analysis this study underscores the need for teacher training programs to emphasize nonverbal skills as essential pedagogical tools. Recommendations for improving teacher awareness and competence in nonverbal communication are also provided.